Evaluating the Selection Factors for Vietnamese Last-Mile Delivery Service Providers using Best Worst Method - Enrico D'agostini (International Journal of Supply Chain Management, 2023)
Recent trends in supply chain show that last mile delivery is one of the fastest growing segments in logistics yet, it remains one the most challenging ones in terms of reliability, cost, and consumers’ requirements. This study aims to identify the factors directly affecting the competitiveness of logistics companies providing last-mile delivery service under a consumers’ perspective. The study employs a best-worst method (BWM) to assess which alternative and which criteria are the preferred ones when selecting a last-mile service provider in Vietnam. The selected criteria include shipping cost, lead-time, customer service, insurance policy and delivery liability, and the alternative are three last-mile service providers namely GHN, GHTK, JT, the largest logistics companies operating in Vietnam. The study findings reveal that GHTK company is the most competitive last-mile service provider compared to the others due to outstanding intrinsic characteristics and competitive advantage. In particular, the findings of the paper show that customer value "Delivery cost" as the most important criterion in domestic last-mile delivery whilst "Customer Service" is the least important one in the Vietnamese market.